The visual language of disquiet: surrealist and expressionist aesthetics in film - Hj Mohammad Razi, Siti Aishah; Jia, Wenxuan; Yaakup, Hani Salwah (Human Resource Management Academic Research Society, 2024)
This research conducts a detailed analysis of the principal artistic concepts associated with Surrealism and Expressionism. It critically reviews classic films through the lens of "artistic medium determinism" and the criteria of "general display logic." Furthermore, the study systematically compiles and reevaluates the aesthetic principles of Surrealist and Expressionist cinema. It also redefines the artistic traits of films within these movements and aims to rectify prevalent misconceptions in contemporary film theory regarding both Surrealism and Expressionism. This comprehensive examination not only revisits classic cinematic examples but also rearticulates the enduring artistic features and theoretical underpinnings of these influential film movement.